Absence of Substantial Copy Number Differences in a Pair of Monozygotic Twins Discordant for Features of Autism Spectrum Disorder - Marina Laplana; José Luis Royo; Anton Aluja; Ricard López; Damiàn Heine-Sunyer; Joan Fibla (Case Reports in Genetics)
Autism spectrum disorder (ASD) is a highly heritable disease (~0.9) with a complex genetic etiology. It is initially characterized by altered cognitive ability which commonly includes impaired language and communication skills as well as fundamental deficits in social interaction. Despite the large amount of studies described so far, the high clinical diversity affecting the autism phenotype remains poorly explained. Recent studies suggest that rare genomic variations, in particular copy number variation (CNV), may account for a significant proportion of the genetic basis of ASD. The use of disease-discordant monozygotic twins represents a powerful strategy to identify de novo and inherited CNV in the disorder. Here we present the results of a comparative genome hybridization (CGH) analysis with a pair of monozygotic twins affected of ASD with significant differences in their clinical manifestations that specially affect speech language impairment and communication skills. Array CGH was performed in three different tissues: blood, saliva, and hair follicle, in an attempt to identify germinal and somatic CNV regions that may explain these differences. Our results argue against a role of large CNV rearrangements as a molecular etiology of the observed differences. This forwards future research to explore de novo point mutation and epigenomic alterations as potential explanations of the observed clinical differences.